How to Design and Harvest a Propeller Flap - Pignatti, Marco; Pinto, Valentina; Docherty Skogh, Ann-Charlott; Giorgini, Federico Armando; Cipriani, Riccardo; De Santis, Giorgio; Hallock, Geoffrey G. (Seminars in Plastic Surgery, 2020)
Propeller flaps are local flaps based either on a subcutaneous pedicle, a single perforator, or vessels entering the flap in such a way so as to allow the flap to rotate on their axis. Depending on the kind of pedicle and the anatomical area, the preoperative investigation and the harvesting techniques may vary.An adequate knowledge of skin and subcutaneous tissue perfusion in the different areas of the body is very important to plan a propeller flap to be successful.The surgeon should begin by finding the most suitable perforators in the area surrounding the defect using available technology. The position, size, and shape of the flap are planned about this point.For perforator-pedicled propeller flaps, the procedure starts with an exploration from the margins of the defect or through a dedicated incision to visualize any perforators in the surroundings. The most suitable perforator is selected and isolated, the skin island is replanned, and the flap is harvested and rotated into the defect. The variations in surgical technique for other types of propellers and in specific anatomical areas are also described.Compared with free flaps, propeller flaps have the advantage of a simpler, shorter operation, without the need for a recipient vessel for microanastomosis.Yet, from a technical point of view, an adequate experience in dissecting perforators and the use of magnifying glasses are almost always required.
Keywords: propeller flap; technique; propeller harvesting; propeller planning